An interval analytic method in constructive existence theorems for initial value problems (2002)
The method of interval analysis is employed to show that the solution, if it exists, of a first order initial value problem is majorised by an interval function whose end- functions satisfy some prescribed conditions. An interval operator is constructed and shown to be a contraction on the majorising interval function. Using this operator, the existence and uniqueness of the solution is established.